(untitled) (Homoeopathy for All, 2022)
The longest and widest nerve of the human body is sciatic nerve. It originates from L4-S3 ventral roots and normally exits the pelvis, via a single trunk, through the great sciatic foramen below the piriformis muscle (PM).1These days sciatica is becoming more common due to wrong sitting posture and sedentary life style. Sciatica is a type of neuralgic pain and can affect any people. Radiating leg pain and related disabilities are common symptoms of it.2Sciatica is known by a range of terms in the literature, such as lumbosacral radicular syndrome, radiculopathy, nerve root pain and nerve root entrapment or irritation.3,4Specifically few studiesare available to examine sciatica, but studies on lower back pain includes data on sciatica prevalence, risk factors, and natural history. It is reported that 5%-10% of patients with low back pain have sciatica and lifetime prevalence of low back pain ranges from 49% to 70%.5Mainstream treatment of sciatica is primarily focused on reduction of pain, either by analgesics or by reducing pressure on the disc. A recent systematic review found that conservative treatments do not clearly improve the natural course of sciatica in most patients or reduce symptoms.6Analgesics,